Effect of consumer innovativeness on new product purchase intentions through learning process and perceived value - Salem A. Al-Jundi; Ahmed Shuhaiber; Reshmi Augustine (Cogent Business & Management, 2019)
Prior research on the impact of consumer innovativeness on new product purchase intentions experienced confusion about the definition of innovativeness and the interest in a specific domain. To fill the gaps, this study builds a new model to examine the multivariate effects of different variables on new product purchase intentions in general and the interplay between all latent variables. We tested a sample of 438 responses that reflect the perspectives of the public in the Emirate of Abu Dhabi, United Arab Emirates, by using partial least squares/structural equation modeling. Substantively, perceived value intercedes in the impact of consumer innovativeness on purchase intentions. Similarly, the learning process mediates the effect of consumer innovativeness on purchase intentions, whereas perceived value mediates the effect of the learning process on purchase intentions. Finally, the learning process and perceived value mediate the effect of consumer innovativeness on new product purchase intentions.
Keywords: C12; C51; M31; D12; O30; O31; 650; new product purchase intention; consumer innovativeness; learning process; perceived value